PELAKSANAAN PARATE EKSEKUSI OBJEK HAK TANGGUNGAN TANPA FIAT PENGADILAN UNTUK MENYELESAIKAN KREDIT BERMASALAH - Vania Nabilah Bani Sonjaya, (Fakultas Hukum Universitas Semarang, 2023)
The purpose of this study is to examine how far the process of parate execution of mortgage rights without court order is regulated in Indonesia to solve non-performing loans and the legal considerations of the invalidity parate execution over the objection filed by the debtor granting the mortgage rights. Parate execution is the power granted by Article 6 and Article 14 paragraph (3) of the Mortgage Rights Law to the first holder of a mortgage rights to execute the mortgage rights on its own power based on the executorial power of the mortgage rights certificate without approval from the debtor granting the mortgage rights and court order. However, the practice of the article has not fully guaranteed legal certainty due to the inconsistency of the Mortgage Rights Law and the incompatibility of legal interpretation so it is important that this research is carried out to avoid repeated misunderstandings. This research is normative juridical that uses a statute and case approach with library research. The results show that the inconsistency of parate execution of mortgage rights still followed the procedure for execution of the grosse mortgage deed regulated in Article 1178 paragraph (2) of the Civil Code and Article 224 HIR/258 RBg, that need approval from the debtor granting the mortgage rights and court order. The application principles of lex posterior derogat legi priori and lex specialis derogat legi generalis, followed by the grammatical interpretation to positive law, affects the progressive aspect of the ease of execution.